Health-Related Quality of Life among Post Myocardial Infarction Patients - Khattab, Omar; Aljeesh, Yousef (KHD-Production, 2024)
The physiological and psychological consequences of myocardial infarction affect the health-related quality of life. This study aimed to assess health-related quality of life among post-myocardial infarction patients at governmental hospitals in the Gaza Strip. The study utilized a descriptive, cross-sectional, analytical design. The sample of the study consisted of 162 post myocardial infarction patients selected by stratified random sampling method. For data collection, the researcher used a self-administered questionnaire of the World Health Organization Quality of Life short version. Statistical analysis included frequency, mean and percentage, as well as independent sample t-test and one-way ANOVA. The results indicated that the study participants have a moderate level of global quality of life (m= 2.94; 58.8%) and moderate satisfaction with their global health (m= 3.01; 60.2%). Moreover, the results indicated moderate physical health (m= 2.79; 55.8%), moderate psychological health (m= 3.06; 61.2%), moderate social relationships (m= 3.22; 64.4%), moderate environmental health (m= 2.77; 55.4%). Overall, the study participants rated their health-related quality of life as moderate level (m= 2.96; 59.2%). The following factors were statistically significant determinants for lower quality of life: being 70 years and older (F= 5.342, P= 0.000), widowed participants (F= 4.135, P value = 0.007), low income (F= 7.436, P value = 0.001), and having other chronic diseases (F= 8.620, P value = 0.000). Factors that were significantly associated with higher quality of life included university education (F= 4.850, P value = 0.009), and working or employed (t= 3.483, P value = 0.001). On the other hand, hospital, gender, family size, and smoking did not have a significant association with quality of life. The study concludes moderate level of quality of life and raised the need to develop strategies to improve quality of life.